Difference between 24-h diet recall and urine excretion for assessing population sodium and potassium intake in adults aged 18–39 y. Issue 2 (17th December 2014) - Mercado, Carla I; Cogswell, Mary E; Valderrama, Amy L; Wang, Chia-Yih; Loria, Catherine M; Moshfegh, Alanna J; Rhodes, Donna G; Carriquiry, Alicia L
ABSTRACT: Background: Limited data are available on the accuracy of 24-h dietary recalls used to monitor US sodium and potassium intakes. Objective: We examined the difference in usual sodium and potassium intakes estimated from 24-h dietary recalls and urine collections. Design: We used data from a cross-sectional study in 402 participants aged 18–39 y ( 50% African American) in the Washington, DC, metropolitan area in 2011. We estimated means and percentiles of usual intakes of daily dietary sodium (dNa) and potassium (dK) and 24-h urine excretion of sodium (uNa) and potassium (uK). We examined Spearman's correlations and differences between estimates from dietary and urine measures. Multiple linear regressions were used to evaluate the factors associated with the difference between dietary and urine measures. Results: Mean differences between diet and urine estimates were higher in men [dNa – uNa (95% CI) = 936.8 (787.1, 1086.5) mg/d and dK – uK = 571.3 (448.3, 694.3) mg/d] than in women [dNa – uNa (95% CI) = 108.3 (11.1, 205.4) mg/d and dK – uK = 163.4 (85.3, 241.5 mg/d)]. Percentile distributions of diet and urine estimates for sodium and potassium differed for men. Spearman's correlations between measures were 0.16 for men and 0.25 for women for sodium and 0.39 for men and 0.29 for women for potassium. Urinary creatinine, total caloric intake, and percentages of nutrient intake from mixed dishes were independently and consistently associated with the differences between diet and urine estimates of sodium and potassium intake. For men, body mass index was also associated. Race was associated with differences in estimates of potassium intake. Conclusions: Low correlations and differences between dietary and urinary sodium or potassium may be due to measurement error in one or both estimates. Future analyses using these methods to assess sodium and potassium intake in relation to health outcomes may consider stratifying by factors associated with the differences in estimates from these methods. This trial was registered at clinicaltrials.gov as NCT01631240.